2019
DOI: 10.1155/2019/4238549
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Pebble Bed Thermal Storage Integrated with Concentrating Parabolic Solar Collector for Cooking

Abstract: Cooking using biomass, which is commonly practiced in developing countries, causes rampant deforestation and exposure to emission. Hence, utilization of solar energy for cooking is a green solution. As solar radiation is not available at every hour of the day, thermal storage is essential for availing thermal energy at required time of use. erefore, this work investigates the e ciency of solar cooker with parabolic concentrating collector integrated with thermal storage using 1D nite di erence computational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The efficiency obtained during the different phases and the overall efficiency of the system are recorded in Table 4. The efficiency value obtained during the charging phase of 76.8%, coincides with that obtained by Singh et al [2], who obtained an average efficiency value between 75-77% in a study on the thermal performance of a packed bed solar storage system for solar air heaters [23]. But it is still lower than that obtained by Ahmet Kurklu et al [24], who obtained an efficiency value of 80% for a solar storage system for heating a greenhouse.…”
Section: Total Energy Stored Energy Dischargedsupporting
confidence: 85%
“…The efficiency obtained during the different phases and the overall efficiency of the system are recorded in Table 4. The efficiency value obtained during the charging phase of 76.8%, coincides with that obtained by Singh et al [2], who obtained an average efficiency value between 75-77% in a study on the thermal performance of a packed bed solar storage system for solar air heaters [23]. But it is still lower than that obtained by Ahmet Kurklu et al [24], who obtained an efficiency value of 80% for a solar storage system for heating a greenhouse.…”
Section: Total Energy Stored Energy Dischargedsupporting
confidence: 85%
“…Stagnation and cooking experiments were done with and without the metal copper chips. Results showed that the maximum temperature achieved was about 118 C in 15 min with 85 g of eggs fried on the receiver with porous medium, whereas the temperature for the plain receiver was only 98 C. Kedida et al [80] analyzed the performance of a pebble bed thermal storage integrated with a concentrating parabolic solar collector for solar cooking. The experimental setup used air as the heat transfer fluid.…”
Section: Parabolic Dish Cookers With Shtesmentioning
confidence: 99%
“…Lee and Rao constructed the three main types of solar cooker and discovered that the parabolic solar cooker achieved the highest temperature at 86.5°C. Moreover, different technologies regarding parabolic solar cookers are being developed throughout the world [52][53][54][55].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As far as the knowledge of the authors is concerned, only a few researches have been conducted regarding the performance of parabolic solar cookers in Ethiopia [55,56]. Moreover, in Ethiopia, a comparison of the parabolic solar cooker with other fuels in terms of cooking time and energy cost has not yet been investigated.…”
Section: Literature Reviewmentioning
confidence: 99%